Freedom from religion and human rights law: strengthening the right to freedom of religion and belief for non-religious and atheist rights-holders - McAdam, Marika (Routledge research in human rights law, 2018)
chapter Introduction -- chapter 1 Freedom of religion or belief -- chapter 2 The hierarchy of religion and belief -- chapter 3 Freedom from proselytism -- chapter 4 Freedom from hate -- chapter 5 Freedom from parents -- chapter 6 Conclusion.